PENGKAJIAN RAKITAN TEKNOLOGI BUDIDAYA KENTANG DAN STRATEGI PENGEMBANGANNYA : Studi Kasus di Wilayah Prima Tani Lahan Kering Dataran Tinggi Kabupaten Magetan - Pudji Santoso; Yuniarti .; Sudarmadi Purnomo; Subandi . (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
Pengkajian Rakitan Teknologi Budidaya Kentang dan Strategi Pengembangannya : Studi Kasus di Wilayah Prima Tani Lahan Kering Dataran Tinggi Kabupaten Magetan. The assessment on improving the cultivation technology of potato as demonstration plot in farmer’s land was done in Prima Tani area of Magetan regency in Genilangit village, during dry season on June – September 2007. Collecting data was done using farm record keeping method on the application of improving cultivation technology of potato which was done by cooperator farmers, while non-cooperator farmers done their potato farming using their own cultivation technology as the comparison. Improving cultivation technologies which were applied by the farmers including 1) Seed quality and seed treatment before planting, 2) The use of rational fertilization, 3) Enlargement of planting space and planting-row space, and 4) Improving pests and diseases control method. The aim of the assessment were 1) To increase productivity, yield quality and farmer’s income of potato farming using the improved cultivation technology, and 2) To find development strategy of potato farming in the assessment area. The result showed, that application of the improved cultivation technology of potato farming can increased productivity, yield quality and farmer’s income. Development strategy for potato farming in this area should be based on the principle of maximize their potency and use their opportunity in facing threats and minimize their weaknesses. Increasing the farming efficiency, productivity and yield quality should be done by application of potato farming using cooperated farming model. The use of qualified seed such as certified potato seed needed to be socialized.